Applying Kingdon's Multiple Streams Framework in the Establishment of Law No.13 of 2012 Concerning the Privilege of Yogyakarta Special Region - Bastian Widyatama (Journal of Government and Civil Society, 2018)
Kingdon’s Multiple Streams, a framework to analyze agenda-setting process is widely considered as a ‘universal’ theoretical framework because of its flexibility to be applied. Therefore, it is necessary to investigate the validity of this ‘universal’ term.By using the case of the establishment of Law No.13 of 2012 concerning the Privilege of Yogyakarta Special Region, this research aims to apply and examine the Kingdon’sframework. The research has been done by using the qualitative method. Interviewing key persons and interpreting written documents are main techniques in data collection process. As the result, this framework remains applicable in the Yogyakarta case. There are 3 factors that brought Yogyakarta issues into the central government’s agenda encompass problem, policy, and politics. Politics is the most dominant factor indicated byYogyakartans strong political movement and Sultanate of Yogyakarta’s political approach. In addition, Sultanate of Yogyakarta canalso be discussed as a policy entrepreneur. As the conclusion, this research has a significant contribution to Kingdon’s multiple streams framework which is still able to explain social phenomena in policy making studies although there are some concerns that need to be explored further, particularly regarding the role of media and policy entrepreneur. Kingdon,s Multiple Streams, sebuah kerangka kerja untuk menganalisis proses agenda setting secara luas dianggap sebagai kerangka kerja 'universal' karena fleksibilitasnya untuk diterapkan. Oleh karena itu, perlu untuk menyelidiki validitas dari istilah 'universal' ini. Dengan menggunakan kasus pembentukan Undang-Undang Nomor 13 Tahun 2012 tentang Hak Istimewa Daerah Istimewa Yogyakarta, penelitian ini bertujuan untuk menerapkan dan memeriksa kerangka kerja Kingdon. Penelitian ini dilakukan dengan menggunakan metode kualitatif. Mewawancarai informan-informan kunci dan menafsirkan dokumen tertulis adalah teknik utama dalam proses pengumpulan data. Akibatnya, kerangka kerja ini tetap berlaku dalam kasus Yogyakarta. Ada 3 faktor yang membawa masalah Yogyakarta ke dalam agenda pemerintah pusat yang mencakup masalah, kebijakan, dan politik. Politik adalah faktor paling dominan yang ditunjukkan oleh gerakan politik kuat orang Yogya dan pendekatan politik Kesultanan Yogyakarta. Selain itu, Kesultanan Yogyakarta juga dapat didiskusikan sebagai pengusaha kebijakan. Sebagai kesimpulan, penelitian ini memiliki kontribusi yang signifikan terhadap kerangka aliran ganda Kingdon yang masih mampu menjelaskan fenomena sosial dalam studi pembuatan kebijakan meskipun ada beberapa kekhawatiran yang perlu dieksplorasi lebih lanjut, terutama mengenai peran media dan pengusaha kebijakan.